Words of Yesterday, Images of Today (Journal of Parents and Teachers, 2025)
The article is based on the University of Santiago and how it came into existence. It also lists a series of regulations that must be followed to access the school, such as the number of students, habits, quality, food, democratic elections, and closing time.
Keywords: schools; regulation; students